Comparative studies on seroepidemiology of canine leptospirosis by micro agglutination test (MAT) and recombinant Lip L32 ELISA - KUMAR, ATUL; SINHA, D K; CHAUDHURY, P; SHANKAR, HARI; SRIVASTAVA, S K (The Indian Journal of Animal Sciences, 2011)
Dogs (806) of 17 breeds were examined serologically by microscopic agglutination test (MAT) for the presence of different serovars of Leptospira organism. An overall seroprevalence of 7.07% was observed by MAT. Serovar Canicola was the predominant followed by lcterohaemorrhagiae, Australis, Autumnalis, Tarassovi, Ballum and others. Male dogs were more sero positive (8.31%) than females (5.41%). The highest seropositivity was observed in 3â€“5 year age group and lowest in under 1 year of age. Breed-wise more number of positive samples were from large sized breed of dogs like Labrador, German shepherd and Doberman. However, Spitz had maximum (26.31%) seroprevalence among all breeds. Sera samples collected from Chennai, Tamil Nadu showed highest seroprevalence (15.21%) with maximum number of serovars (28). The efficacy of recombinant leptospiral lipoprotein 32 (rLipL32) as an antigen was evaluated using enzyme-linked immunosorbent assay (ELISA) for serodiagnosis of canine leptospirosis. A seropositivity of 10.29% was observed. The relative sensitivity and specificity of ELISA as compared to MAT, was calculated as 100 and 96.52%, respectively. The concordance percentage between MAT and ELISA was 96.77, and the kappa statistics showed a substantial amount of agreement between MAT and ELISA. Results suggested that rLipL32 protein antigen based ELISA could be used as a serodiagnostic test for serodiagnosis of canine leptospirosis.Â